Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment

By coating the lithium-rich manganese-based positive electrode active material, secondary particles with a cladding layer are formed, which solves the problem of taking into account both the circulation performance and the volume energy density in the prior art, and achieves the high energy density and excellent circulation performance of the battery .

CN119297264APending Publication Date: 2025-01-10BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411392087.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode active materials cannot take into account both the circulation performance and volume energy density, and the increase in porosity during the charging and discharging process leads to a decrease in the compaction density, affecting the energy density of the battery.

Method used

By first sintering the lithium-rich manganese-based precursor, the lithium source and the M1 source, the matrix material is formed, and then coated with the M2 source and the solvent, secondary particles with the coating layer are formed, and the acid solution soaking conditions are controlled. To improve the specific surface area and porosity changes, the full contact and interface stability of the positive electrode active material and the electrolyte are achieved.

Benefits of technology

It improves the cycling performance and volume energy density of the battery, while maintaining high compaction density and lattice integrity, extending the cycling stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297264A_ABST
    Figure CN119297264A_ABST
Patent Text Reader

Abstract

The invention discloses a positive active material and a preparation method thereof, a positive pole piece, a battery and electric equipment, the positive active material satisfies the following conditions: [delta] BET = BET2-BET1, [delta] BET is greater than or equal to 1m < 2 > / g and less than or equal to 3.45 m < 2 > / g, [delta] P = P2-P1, and [delta] P is greater than or equal to 0.7% and less than or equal to 1.9%, BET1 is the specific surface area of the positive active material before being soaked in an acid solution, and BET is the specific surface area of the positive active material before being soaked in the acid solution. BET2 is the specific surface area of the positive electrode active material after being soaked in the acid solution, P1 is the porosity of the positive electrode active material before being soaked in the acid solution, P2 is the porosity of the positive electrode active material after being soaked in the acid solution, the weight ratio of the positive electrode active material to the acid solution is 1: 10, and P1 is the specific surface area of the positive electrode active material after being soaked in the acid solution. The pH value of the acidic solution is 5.5, and the soaking time is 2 hours. Therefore, after the positive electrode active material provided by the invention is soaked in an acid solution, the increase rate (delta BET) of the specific surface area of the positive electrode active material is relatively large on the premise that the porosity change is relatively small, so that the energy density and the cycle performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular, to positive electrode active materials and preparation methods thereof, positive electrode sheets, batteries, and electrical equipment. Background Art

[0002] Lithium-rich manganese-based positive electrode active materials have become a research hotspot in the field of lithium-ion battery positive electrodes due to their high specific capacity and high energy density. Lithium-rich manganese-based positive electrode active materials contain Ni, Co, and Mn elements, with a specific capacity of more than 240mAh / g, an average voltage of more than 3.5V, and an energy density higher than layered LiMO2, spinel-type LiMn2O4, and olivine-type LiFePO4. Therefore, lithium-rich manganese-based positive electrode active materials are regarded as the preferred materials for the next generation of lithium-ion battery positive electrode active materials. However, the positive electrode active materials in the related art cannot take into account both their cycle performance and volume energy density. Summary of the invention

[0003] The present application aims to solve one of the technical problems in the related art at least to some extent.

[0004] In a first aspect, the present application provides a positive electrode active material, wherein the positive electrode active material is a secondary particle formed by agglomeration of primary particles, at least part of the surface of the secondary particle has a coating layer, the secondary particle includes pores, and the positive electrode active material satisfies: ΔBET=BET2-BET1, 1m 2 / g≤ΔBET≤3.45m 2 / g, ΔP=P2-P1, 0.7%≤ΔP≤1.9%, wherein BET1 is the specific surface area of ​​the positive electrode active material before immersion in the acidic solution, BET2 is the specific surface area of ​​the positive electrode active material after immersion in the acidic solution, P1 is the porosity of the positive electrode active material before immersion in the acidic solution, P2 is the porosity of the positive electrode active material after immersion in the acidic solution, the weight ratio of the positive electrode active material to the acidic solution is 1:10, the pH of the acidic solution is 5.5, and the immersion time is 2h. Therefore, the surface of the positive electrode active material proposed in the present application has a coating layer, which can improve the interfacial stability between the positive electrode active material and the electrolyte. After immersion in an acidic solution, the porosity of the positive electrode active material changes little, and the increase rate of specific surface area (ΔBET) is large. During the battery charging and discharging process, the positive electrode active material can be in contact with the electrolyte more fully, thereby promoting the interfacial reaction between the positive electrode active material and the electrolyte, and obtaining a battery with both high energy density and excellent cycle performance.

[0005] According to some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions: 1.75 m 2 / g≤BET2≤4m 2 / g; 0.55m 2 / g≤BET1≤1.85m 2 / g.

[0006] According to some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions: 1.9%≤P1≤4%; 2.6%≤P2≤6.5%.

[0007] According to some embodiments of the present application, the positive electrode active material satisfies: ΔDp=Dp1-Dp2, 7nm≤ΔDp≤13nm, wherein Dp1 is the average pore size of the positive electrode active material before the positive electrode active material is immersed in the acidic solution, and Dp2 is the average pore size of the positive electrode active material after the positive electrode active material is immersed in the acidic solution. Thus, the average pore size of the positive electrode active material after being immersed in the acidic solution is reduced, and the specific surface area of ​​the positive electrode active material can be increased with a small change in porosity, thereby improving the energy density and cycle performance of the battery.

[0008] According to some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions: 16nm≤Dp1≤36nm; 9nm≤Dp2≤25nm. As a result, the average pore size of the positive electrode active material tends to decrease, and the specific surface area of ​​the positive electrode active material can be increased with a small change in porosity, thereby improving the energy density and cycle performance of the battery.

[0009] According to some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions: before the positive electrode active material is immersed in the acidic solution, the pore size of the pore size less than or equal to 10nm accounts for 33%-60%; after the positive electrode active material is immersed in the acidic solution, the pore size of the pore size less than or equal to 10nm accounts for 50%-80%. Thus, the specific surface area of ​​the positive electrode active material is increased, and the cycle performance of the battery is improved.

[0010] According to some embodiments of the present application, the compaction density of the positive electrode active material is 2.7 g / cm 3 -3.2g / cm 3 . Thus, the energy density of the battery is improved.

[0011] According to some embodiments of the present application, the positive electrode active material satisfies: η=FWHM(104) / FWHM(003), 1.8≤η≤2.8, optionally, 1.85≤η≤2.1, wherein FWHM(104) is the half-peak width of the diffraction peak (104) of the X-ray diffraction spectrum, and the 2θ value corresponding to the diffraction peak (104) is 43.5°-45.5°, and FWHM(003) is the half-peak width of the diffraction peak (003) of the X-ray diffraction spectrum, and the 2θ value corresponding to the diffraction peak (003) is 17.5°-19.5°. This indicates that the positive electrode active material in the present application has good lattice integrity, which can improve the cycle stability of the positive electrode active material.

[0012] According to some embodiments of the present application, the positive electrode active material includes a compound represented by Formula I: Li 1+δ (Ni x(1-a) Co y(1-a) Li (1-2x-y)(1-a) / 3 Mn (2-x-y)(1-a) / 3 M 1 a M 2 b ) (2+δ / 2) N n Formula I, wherein 0.02≤δ≤0.08, 0.25≤x≤0.45, 0≤y≤0.1, 0≤a≤0.035, 0<b≤0.04, 0≤n≤0.04, M 1 Including at least one of Al, Zr, Y, Mg, Ti, W, Si, Yb, Nb, Sc, Ca, La, Sr, Y, M 2 It includes at least one of B, Mg, Al, Ti, V, Sr, Y, Zr, Nb, Mo, Sc, Cr, La, Sr, and W, and N includes at least one of F, S, P, and O.

[0013] According to some embodiments of the present application, at least one of the following conditions is satisfied: 0.03≤δ≤0.06; 0.001≤a≤0.02; 0.001≤b≤0.02; 0≤n≤0.02.

[0014] According to some embodiments of the present application, the coating layer includes M 2 Thus, the interface stability between the positive electrode active material and the electrolyte is improved, and the cycle performance of the battery is improved.

[0015] The second aspect of the present application provides a method for preparing a positive electrode active material, the method comprising: mixing a lithium-rich manganese-based precursor, a lithium source, and M 1 The matrix material, M 2 The source and solvent are mixed for coating treatment, and the M 2The particle size D50 of the source is 20nm-700nm, the solid-liquid ratio of the matrix material to the solvent is 0.3g / mL-3.5g / mL, the solid-liquid separation is carried out, and the solid phase material is dried to obtain a matrix material having a coating layer on at least part of the surface; the matrix material having the coating layer is subjected to a second sintering, and the temperature of the second sintering is less than or equal to the temperature of the first sintering, to obtain the positive electrode active material. Thus, the soluble residual substances in the pores between the primary particles can be washed to the outside of the secondary particles during the coating process, and the coating agent M can be controlled by controlling the solid-liquid ratio of the coating process and the coating agent M. 2 The particle size D50 of the source controls the depth and degree of flushing, so that more micropores are formed inside the secondary particles, so that after the positive electrode active material is immersed in an acidic solution, the porosity changes little, but the specific surface area increase rate (ΔBET) is large, thereby obtaining a battery with both excellent cycle performance and high volume energy density.

[0016] According to some embodiments of the present application, the coating treatment temperature is 8° C.-37° C. Thus, the positive electrode active material has a larger specific surface area under the premise of a smaller change in porosity, thereby improving the cycle performance of the battery.

[0017] According to some embodiments of the present application, the coating treatment time is 30s-1200s, and can be optionally 60s-600s.

[0018] According to some embodiments of the present application, the molar content of lithium in the lithium source is n1, and the molar content of Ni, Co, Mn, Mn in the lithium-rich manganese-based precursor is n1. 1 The total molar content of the elements is n2, and satisfies: 1.12≤n1 / n2≤1.49. Thus, the integrity of the positive electrode active material lattice is improved, and the cycle stability of the positive electrode active material is improved.

[0019] According to some embodiments of the present application, the M 2 Source M 2 The molar content of the element is n3, and satisfies 0≤n3 / n2≤0.05, optionally, 0.001≤n3 / n2≤0.02.

[0020] According to some embodiments of the present application, the method satisfies at least one of the following conditions: the temperature of the first sintering is 800°C-980°C; the time of the first sintering is 5h-15h; the heating rate of the first sintering is 1.3°C / min-10°C / min.

[0021] According to some embodiments of the present application, at least one of the following conditions is met: the temperature of the second sintering is 300° C.-800° C.; the time of the second sintering is 6 h-20 h.

[0022] According to some embodiments of the present application, the precursor includes a compound represented by formula II:

[0023] Ni x Co y Mn z (OH)2 Formula II,

[0024] Among them, 0.25≤x≤0.45, 0≤y≤0.10, z=1-xy.

[0025] According to some embodiments of the present application, the method satisfies at least one of the following conditions: 1 Sources include M 1 Oxide, M 1 Sulfide, M 1 Fluoride, M 1 The hydroxide, M 1 At least one of the carbonates of 2 Sources include M 2 Oxide, M 2 Sulfide, M 2 Fluoride, M 2 The hydroxide, M 2 Carbonate, M 2 Thus, by doping M in the positive electrode active material 1 elements, which can improve the structural stability of the positive electrode active material; by forming a layer containing M on at least part of the surface of the positive electrode active material matrix 2 The coating layer improves the structural stability of the positive electrode active material and the interface stability between the positive electrode active material and the electrolyte.

[0026] The third aspect of the present application provides a positive electrode plate, comprising the positive electrode active material provided in the first aspect of the present application or the positive electrode active material prepared by the method provided in the second aspect of the present application.

[0027] The fourth aspect of the present application provides a battery, comprising the positive electrode sheet provided in the third aspect of the present application. Thus, the battery has a high volume energy density and excellent cycle performance.

[0028] The fifth aspect of the present application provides an electrical device, including the battery provided by the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0030] Figure 1A schematic flow chart of a method for preparing a positive electrode active material according to an embodiment of the present application is shown. DETAILED DESCRIPTION

[0031] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0032] For lithium-rich manganese-based positive electrode active materials, increasing their specific surface area can make the contact between the positive electrode active materials and the electrolyte more complete, promote the interfacial reaction between the positive electrode active materials and the electrolyte, and improve the battery's cycle performance. However, the increase in the specific surface area of ​​lithium-rich manganese-based positive electrode active materials in the related art is accompanied by an increase in porosity. After the porosity increases, the compaction density of the lithium-rich manganese-based positive electrode active materials decreases, sacrificing the battery's energy density. In other words, it is impossible to obtain a lithium-rich manganese-based positive electrode active material with both high energy density and excellent cycle performance.

[0033] In a first aspect, the present application provides a positive electrode active material, wherein the positive electrode active material is a secondary particle formed by agglomeration of primary particles, at least part of the surface of the secondary particle has a coating layer, the secondary particle includes pores, and the positive electrode active material satisfies: ΔBET=BET2-BET1, 1m 2 / g≤ΔBET≤3.45m 2 / g, ΔP=P2-P1, 0.7%≤ΔP≤1.9%, wherein BET1 is the specific surface area of ​​the positive electrode active material before immersion in the acidic solution, BET2 is the specific surface area of ​​the positive electrode active material after immersion in the acidic solution, P1 is the porosity of the positive electrode active material before immersion in the acidic solution, P2 is the porosity of the positive electrode active material after immersion in the acidic solution, the weight ratio of the positive electrode active material to the acidic solution is 1:10, the pH of the acidic solution is 5.5, and the immersion time is 2h.

[0034] During the operation of the battery, the positive electrode active material will be fully infiltrated by the electrolyte, and the coating layer on the surface of the secondary particles of the positive electrode active material will be infiltrated by the electrolyte, thereby exposing the holes inside the secondary particles, and the porosity and specific surface area of ​​the positive electrode active material will increase with the appearance of new holes. After the positive electrode active material proposed in this application is immersed in an acidic solution simulating the electrolyte, the porosity changes little, but the increase rate of the BET specific surface area (ΔBET) is large, which means that during the operation of the battery, after the positive electrode active material is fully infiltrated by the electrolyte, it can have a larger specific surface area while maintaining a low porosity, thereby shortening the diffusion path of lithium ions in the positive electrode active material, increasing the gram capacity of the positive electrode active material, and making the positive electrode active material more fully in contact with the electrolyte during the battery charge and discharge process, thereby promoting the interface reaction between the positive electrode active material and the electrolyte, and improving the cycle performance of the battery.

[0035] The positive electrode active material proposed in the present application has a coating layer, and the coating layer can improve the interface stability between the positive electrode active material and the electrolyte, thereby improving the cycle performance of the battery.

[0036] As an example, ΔBET can be 1 m 2 / g, 1.75m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.45m 2 / g, etc., or may be within the range consisting of any of the above values.

[0037] In the present application, BET1 can be obtained by testing using Micromeritics' Tristar 3020 surface area analyzer. The testing method for BET2 is to immerse the positive electrode active material in an acidic solution for 2 hours, the weight ratio of the positive electrode active material to the acidic solution is 1:10, and the pH of the acidic solution is 5.5. After immersion, it is dried at 120°C in a vacuum and tested using the BET1 method.

[0038] As an example, ΔP may be 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, etc., or may be a range consisting of any of the above values.

[0039] In the present application, P1 can be directly obtained by testing with Micromeritics' Tristar 3020 surface area analyzer. The testing method of P2 is to immerse the positive electrode active material in an acidic solution for 2 hours, the weight ratio of the positive electrode active material to the acidic solution is 1:10, and the pH of the acidic solution is 5.5. After immersion, it is dried at 120°C in a vacuum and tested using the method of P1.

[0040] According to some embodiments of the present application, 1.75m 2 / g≤BET2≤4m 2 / g, for example, can be 1.75m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, etc., or may be within the range consisting of any of the above values.

[0041] According to some embodiments of the present application, 0.55m 2 / g≤BET1≤1.85m 2 / g, for example, can be 0.55m 2 / g, 0.75m 2 / g, 0.95m 2 / g, 1.15m 2 / g, 1.35m 2 / g, 1.55m 2 / g, 1.85m 2 / g, etc., or may be within the range consisting of any of the above values.

[0042] Thus, by making BET2 and BET1 within the above range, the contact area between the positive electrode active material and the electrolyte can be increased, achieving Li + It can quickly embed and eject the positive electrode, and at the same time prevent the excessive contact area from causing the crystal structure to be destroyed during the cycle, thereby reducing the impact on the cycle performance of the positive electrode active material.

[0043] According to some embodiments of the present application, 1.9%≤P1≤4%, for example, it can be 1.9%, 2.3%, 2.7%, 3.1%, 3.5%, 3.7%, 4%, etc., or it can be a range consisting of any of the above values.

[0044] According to some embodiments of the present application, 2.6%≤P2≤6.5%, for example, it can be 2.6%, 3%, 3.4%, 3.8%, 4.2%, 4.6%, 5%, 5.4%, 5.8%, 6.2%, 6.5%, etc., or it can be a range consisting of any of the above numerical values.

[0045] Therefore, by making P1 within the above range, the bulk density of the secondary particles is increased, thereby increasing the compaction density of the positive electrode active material; by making P2 within the above range, the positive electrode active material can be fully in contact with the electrolyte, thereby reducing the impedance of the battery.

[0046] According to some embodiments of the present application, the positive electrode active material satisfies: ΔDp=Dp1-Dp2, 7nm≤ΔDp≤13nm, wherein Dp1 is the average pore size of the positive electrode active material before the positive electrode active material is immersed in the acidic solution, and Dp2 is the average pore size of the positive electrode active material after the positive electrode active material is immersed in the acidic solution. Thus, after being immersed in the acidic solution, the average pore size of the positive electrode active material decreases, that is, during the battery cycle, after the positive electrode active material is fully infiltrated by the electrolyte, the porosity changes less but the average pore size decreases, thereby increasing the specific surface area of ​​the positive electrode active material, making the contact between the positive electrode active material and the electrolyte more complete, and thus obtaining a battery with both high energy density and excellent cycle performance.

[0047] As an example, ΔDp may be 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, etc., or may be a range consisting of any of the above values.

[0048] According to some embodiments of the present application, 16nm≤Dp1≤36nm, for example, it can be 16nm, 20nm, 24nm, 28nm, 32nm, 36nm, etc., or can be a range consisting of any of the above numerical values.

[0049] According to some embodiments of the present application, 9nm≤Dp2≤25nm, for example, it can be 9nm, 13nm, 17nm, 21nm, 25nm, etc., or can be a range consisting of any of the above numerical values.

[0050] As a result, the average pore size of the positive electrode active material tends to decrease, which can increase the specific surface area of ​​the positive electrode active material with a small change in porosity, thereby improving the energy density and cycle performance of the battery.

[0051] According to some embodiments of the present application, before the positive electrode active material is immersed in the acidic solution, the proportion of pores with a pore diameter less than or equal to 10 nm is 33%-60%; for example, it can be 33%, 37%, 41%, 45%, 49%, 54%, 57%, 60%, etc., or it can be a range composed of any of the above numerical values.

[0052] In the present application, the proportion of pores with a pore size of less than or equal to 10 nm refers to the proportion of the sum of the specific surface areas of pores with a pore size of less than or equal to 10 nm in the total specific surface area of ​​the secondary particles.

[0053] According to some embodiments of the present application, after the positive electrode active material is immersed in the acidic solution, the pore size of pores less than or equal to 10 nm accounts for 50%-80%. For example, it can be 50%, 60%, 70%, 80%, etc., or can be a range composed of any of the above values.

[0054] Therefore, after soaking in an acidic solution, the proportion of small pores increases. The smaller the pore size, the larger the specific surface area of ​​the positive electrode active material. More small-sized pores can increase the specific surface area of ​​the positive electrode active material, promote the interfacial reaction between the positive electrode active material and the electrolyte, and improve the battery's cycle performance.

[0055] According to some embodiments of the present application, the compaction density of the positive electrode active material can be 2.7 g / cm 3 -3.2g / cm 3 For example, it can be 2.7 g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 , 3g / cm 3 、3.1g / cm 3 、3.2g / cm 3 The energy density of the battery is thereby increased.

[0056] According to some embodiments of the present application, the positive electrode active material includes a compound shown in Formula I:

[0057] Li 1+δ (Ni x(1-a) Co y(1-a) Li (1-2x-y)(1-a) / 3 Mn (2-x-y)(1-a) / 3 M 1 a M 2 b ) (2+δ / 2) N n Formula I,

[0058] Among them, 0.02≤δ≤0.08, 0.25≤x≤0.45, 0≤y≤0.1, 0≤a≤0.035, 0<b≤0.04, 0≤n≤0.04, M 1 Including at least one of Al, Zr, Y, Mg, Ti, W, Si, Yb, Nb, Sc, Ca, La, Sr, Y, M 2 It includes at least one of B, Mg, Al, Ti, V, Sr, Y, Zr, Nb, Mo, Sc, Cr, La, Sr, and W, and N includes at least one of F, S, P, and O.

[0059] As an example, δ may be 0.002, 0.004, 0.006, 0.008, etc., or may be a range consisting of any of the above values. According to some specific embodiments of the present application, 0.03≤δ≤0.06.

[0060] As an example, x may be 0.25, 0.3, 0.35, 0.4, 0.45, etc., or may be a range consisting of any of the above values.

[0061] As an example, y may be 0, 0.03, 0.05, 0.07, 0.1, etc., or may be a range consisting of any of the above values.

[0062] As an example, a may be 0, 0.01, 0.02, 0.03, 0.035, etc., or may be a range consisting of any of the above values. According to some specific embodiments of the present application, 0.001≤a≤0.02.

[0063] As an example, b can be 0, 0.01, 0.02, 0.03, 0.04, etc., or can be a range consisting of any of the above values. According to some specific embodiments of the present application, 0.001≤b≤0.02.

[0064] As an example, n can be 0, 0.005, 0.01, 0.015, 0.02, etc., or can be a range consisting of any of the above values. According to some specific embodiments of the present application, 0≤n≤0.02.

[0065] According to some embodiments of the present application, the positive electrode active material satisfies: η=FWHM(104) / FWHM(003), 1.8≤η≤2.8, wherein FWHM(104) is the half-peak width of the diffraction peak (104) of the X-ray diffraction spectrum, and the 2θ value corresponding to the diffraction peak (104) is 43.5°-45.5°, and FWHM(003) is the half-peak width of the diffraction peak (003) of the X-ray diffraction spectrum, and the 2θ value corresponding to the diffraction peak (003) is 17.5°-19.5°. For example, η can be 1.8, 2, 2.2, 2.4, 2.6, 2.8, etc., or can be a range consisting of any of the above values.

[0066] The symmetry of the (003) plane in the X-ray diffraction spectrum of the positive electrode active material is more obvious than that of the (104) plane. When the ratio of FWHM (104) / FWHM (003) is within the range specified in the present application, it indicates that part of the Li atoms are distributed in the transition metal layer of the lattice, that is, the Li atoms with a content of (1-2x-y) (1-a) / 3 in Formula I enter the lattice, and the lattice integrity of the positive electrode active material of the present application is better and the cycle stability is better. According to some specific embodiments of the present application, 1.85≤η≤2.1.

[0067] In the present application, FWHM (104) and FWHM (003) can be obtained by testing with a Smart Lab 9KW X-ray diffractometer of Rigaku Corporation.

[0068] According to some embodiments of the present application, the coating layer includes M 2 element.

[0069] The second aspect of the present application provides a method for preparing a positive electrode active material, the method comprising: mixing a lithium-rich manganese-based precursor, a lithium source, M 1 The matrix material, M 2 The source and solvent are mixed for coating treatment, and the M 2 The particle size D50 of the source is 20nm-700nm, the solid-liquid ratio of the matrix material to the solvent is 0.3g / mL-3.5g / mL, the solid-liquid separation is carried out, and the solid phase material is dried to obtain a matrix material having a coating layer on at least part of the surface; the matrix material having the coating layer is subjected to a second sintering, and the temperature of the second sintering is less than or equal to the temperature of the first sintering, to obtain the positive electrode active material. Thus, during the coating process, the soluble residual substances in the pores between the primary particles can be washed to the outside of the secondary particles, and by controlling the solid-liquid ratio of the coating process and the coating agent M 2 The particle size D50 of the source controls the depth and degree of flushing, so that more micropores are formed inside the secondary particles, so that after the positive electrode active material is immersed in an acidic solution, the porosity changes little, but the specific surface area increase rate (ΔBET) is large, thereby obtaining a battery with both excellent cycle performance and high volume energy density.

[0070] The following is a detailed description of this method, see Figure 1 , the method comprising:

[0071] S10: Li-rich manganese-based precursor, lithium source, M 1 The source mixture is first sintered to obtain the matrix material

[0072] According to some embodiments of the present application, the precursor includes a compound represented by formula II:

[0073] Ni x Co y Mn z (OH)2 Formula II,

[0074] Among them, 0.25≤x≤0.45, 0≤y≤0.10, z=1-xy.

[0075] According to some embodiments of the present application, the lithium source may include at least one of lithium carbonate and lithium hydroxide.

[0076] According to some embodiments of the present application, the M 1 Sources include M 1 Oxide, M 1 Sulfide, M1 Fluoride, M 1 Hydroxide, M 1 at least one of the carbonates.

[0077] According to some embodiments of the present application, the molar content of lithium in the lithium source is n1, and the molar content of Ni, Co, Mn, Mn in the lithium-rich manganese-based precursor is n1. 1 The total molar content of the elements is n2, and satisfies: 1.12≤n1 / n2≤1.49. Thus, the integrity of the positive electrode active material lattice is improved, and the cycle stability of the positive electrode active material is improved.

[0078] As an example, n1 / n2 may be 1.12, 1.2, 1.25, 1.3, 1.35, 1.4, 1.49, etc., or may be a range of any of the above values. Thus, the integrity of the positive electrode active material lattice is improved, and the cycle stability of the positive electrode active material is improved.

[0079] According to some embodiments of the present application, the heating rate V1 of the first sintering may satisfy 1.3°C / min≤V1≤10°C / min, for example, it may be 1.3°C / min, 6°C / min, 8°C / min, 10°C / min, etc., or it may be a range consisting of any of the above values.

[0080] According to some embodiments of the present application, the temperature of the first sintering is T1 and satisfies 800℃≤T1≤980℃. For example, it can be 800℃, 840℃, 880℃, 920℃, 960℃, 980℃, etc., or can be a range consisting of any of the above numerical values.

[0081] According to some embodiments of the present application, the time of the first sintering is t1, satisfying 5h≤t1≤15h. For example, it can be 5h, 7h, 9h, 11h, 13h, 15h, etc., or can be a range consisting of any of the above values.

[0082] S20: The base material, M 2 The source and solvent are mixed for coating treatment, and the M 2 The particle size D50 of the source is 20nm-700nm, the solid-liquid ratio of the matrix material to the solvent is 0.3g / mL-3.5g / mL, the solid-liquid separation is performed, and the solid phase material is dried to obtain a matrix material having a coating layer on at least part of the surface

[0083] According to some embodiments of the present application, the base material, M 2 The sources are sequentially added into the aqueous solution for coating treatment, and solid-liquid separation is performed to obtain a solid phase substance, and the solid phase substance is dried to obtain a base material with a coating layer.

[0084] According to some embodiments of the present application, the M 2 The particle size D50 of the source is 20nm-700nm, for example, 20nm, 100nm, 300nm, 500nm, 700nm, etc., or can be any range of the above values. 2 The source can better flush the pores between primary particles to form more micropores.

[0085] If M 2 If the particle size D50 of the source is too small, it is easy to block the holes on the surface of the secondary particles and reduce the specific surface area of ​​the positive electrode active material; 2 If the particle size D50 of the source is too large, it cannot enter the pores between the primary particles, which will reduce the flushing effect and also reduce the specific surface area of ​​the positive electrode active material.

[0086] According to some embodiments of the present application, the solid-liquid ratio of the matrix material to the solvent can be 0.5g / mL, 1g / mL, 1.5g / mL, 2g / mL, 2.5g / mL, 3g / mL, 3.5g / mL, etc., or can be a range composed of any of the above values. By making the solid-liquid ratio within the above range, the pores between the primary particles can be better washed to form more micropores, so that the porosity of the positive electrode active material after being soaked in an acidic solution changes little, the specific surface area increases more, and the volume energy density and cycle performance of the battery are improved.

[0087] If the solid-liquid ratio is too small or too large, the fillers between the primary particles cannot be completely washed away, the number of micropores inside the secondary particles is reduced, and the specific surface area increase rate and porosity change rate of the positive electrode active material before and after immersion in the acid solution are small, which has limited improvement on the battery's cycle performance.

[0088] According to some embodiments of the present application, the coating treatment temperature is 8° C.-37° C. For example, it can be 8° C., 10° C., 15° C., 20° C., 25° C., 30° C., 37° C., etc., or can be a range consisting of any of the above values.

[0089] According to some embodiments of the present application, the coating treatment time is 30s-1200s, for example, 30s, 100s, 300s, 500s, 700s, 900s, 1100s, 1200s, etc., or can be a range composed of any of the above values. According to some specific embodiments of the present application, the coating treatment time is 60s-600s.

[0090] According to some embodiments of the present application, the M 2 Source M 2The molar content of the element is n3, and satisfies 0≤n3 / n2≤0.05, for example, it can be 0, 0.01, 0.02, 0.03, 0.05, etc., or can be a range consisting of any of the above values. According to some specific embodiments of the present application, 0.001≤n3 / n2≤0.02.

[0091] According to some embodiments of the present application, the M 2 Sources include M 2 Oxide, M 2 Sulfide, M 2 Fluoride, M 2 The hydroxide, M 2 Carbonate, M 2 At least one of the oxyhydroxides.

[0092] S30: performing a second sintering on the base material with the coating layer, wherein the temperature of the second sintering is less than or equal to the temperature of the first sintering, so as to obtain the positive electrode active material

[0093] According to some embodiments of the present application, the base material with the coating layer is sintered for a second time in an oxygen-containing atmosphere to obtain a secondary sintered product, and the secondary sintered product is screened and iron-removed to obtain the positive electrode active material.

[0094] According to some embodiments of the present application, the temperature of the second sintering is T2 and satisfies 300℃≤T2≤800℃. For example, it can be 300℃, 400℃, 500℃, 600℃, 700℃, 800℃, etc., or can be a range consisting of any of the above numerical values.

[0095] According to some embodiments of the present application, the second sintering time is t2, and satisfies 6h≤t2≤20h. For example, it can be 6h, 10h, 14h, 18h, 20h, etc., or can be a range consisting of any of the above values.

[0096] Therefore, by performing the first sintering and the second sintering under the above conditions, the small micropores generated in the secondary particles during the coating process can be retained to the greatest extent.

[0097] In summary, the positive electrode active material proposed in this application has the following advantages:

[0098] (1) The positive electrode active material proposed in the present application has a coating layer on its surface. After the simulated electrolyte infiltration process, the acidic solution can penetrate the coating layer, thereby changing the specific surface area, porosity, etc. of the positive electrode active material. The change in porosity of the positive electrode active material is small, and the increase rate of specific surface area (ΔBET) is large, indicating that there are a large number of small-sized pores inside the positive electrode active material, thereby improving the energy density and cycle performance of the battery.

[0099] (2) Since the positive electrode active material has a large specific surface area, the positive electrode active material can be fully in contact with the electrolyte, promoting the interfacial reaction between the positive electrode active material and the electrolyte and improving the cycle performance of the battery.

[0100] (3) After the simulated electrolyte infiltration process, the average pore size of the positive electrode active material is small. These small pore sizes can enable the positive electrode active material to have a larger specific surface area under the condition of lower porosity, thereby obtaining a positive electrode active material with both higher compaction density and excellent cycle performance;

[0101] (4) The positive electrode active material proposed in this application has good lattice integrity, which can further improve the cycle performance of the battery.

[0102] (5) In the process of preparing the positive electrode active material, the present invention controls the solid-liquid ratio and the coating agent M of the coating process. 2 The particle size D50 of the source controls the depth and degree of flushing, so that more micropores are formed inside the secondary particles, so that after the positive electrode active material is immersed in an acidic solution, the porosity changes little, but the specific surface area increase rate (ΔBET) is large, thereby obtaining a battery with both excellent cycle performance and high volume energy density.

[0103] The third aspect of the present application provides a positive electrode plate, comprising the positive electrode active material provided in the first aspect of the present application or the positive electrode active material prepared by the method provided in the second aspect of the present application.

[0104] The fourth aspect of the present application provides a battery, comprising the positive electrode sheet provided in the third aspect of the present application. Thus, the battery has a higher volume energy density and cycle performance.

[0105] The fifth aspect of the present application provides an electrical device, including the battery provided by the fourth aspect of the present application.

[0106] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0107] Example 1

[0108] 1. Preparation of positive electrode active materials

[0109] (1) Li-rich manganese-based precursor (Ni 0.33 Co 0.06 Mn 0.61(OH)2), lithium carbonate and TiO2 are mixed and sintered for the first time. The sintering atmosphere is air. The heating rate is 3°C / min. The first sintering time is 9h. The first sintering temperature is 890°C. After naturally cooling to room temperature, the material is crushed and sieved to obtain a matrix material.

[0110] (2) The matrix material Li 1.04 (Ni 0.287 Co 0.052 Li 0.122 Mn 0.531 Ti 0.007 ) 2.020 Mixed with deionized water and AlF for coating treatment, the particle size D50 of AlF is 200nm, the solid-liquid ratio of the matrix material to deionized water is 1.5g / mL, the coating temperature is 14°C, the coating time is 3400s, and the coated product is obtained after filter pressing and vacuum drying;

[0111] (3) The coated product is sintered for a second time in an air atmosphere at a temperature of 400°C for 10 hours, and then sieved and iron-removed, and cooled naturally to room temperature to obtain Li 1.04 (Ni 0.287 Co 0.0452 Li 0.122 Mn 0.531 Ti 0.007 )Al 0.010 O 2.025 F 0.010 .

[0112] 2. Preparation of positive electrode sheet

[0113] The positive electrode active material Li prepared in Example 1 1.04 (Ni 0.287 Co 0.0452 Li 0.122 Mn 0.531 Ti 0.007 )Al 0.010 O 2.025 F 0.010 , polyvinylidene fluoride (PVDF), and acetylene black are mixed with an appropriate amount of N-methylpyrrolidone (NMP) in a mass ratio of 90:5:5 to form a uniform slurry, the slurry is coated on an aluminum foil and dried, and then stamped into a positive electrode sheet with a diameter of 12 mm and a thickness of 120 μm at a pressure of 100 MPa, and then the positive electrode sheet is placed in a vacuum drying oven at 120°C and dried for 12 hours.

[0114] 3. Preparation of negative electrode sheet

[0115] The negative electrode uses a Li metal sheet with a diameter of 17 mm and a thickness of 1 mm.

[0116] 4. Isolation film

[0117] A polyethylene porous membrane with a thickness of 25 μm.

[0118] 5. Electrolyte

[0119] An equal volume mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1 mol / L LiPF6 as the electrolyte.

[0120] 6. Assemble the battery

[0121] The positive electrode plate, the isolation membrane, the negative electrode plate and the electrolyte were assembled into a 2025 type button battery in an Ar gas glove box with a water content and an oxygen content both less than 5 ppm.

[0122] The preparation process of the positive electrode active material in Examples 2 to 8 is shown in Table 1. The preparation method of the battery in Examples 2 to 8 is the same as that in Example 1.

[0123] Example 7

[0124] The preparation method of the positive electrode active material is the same as that in the embodiment, except that the amount of lithium carbonate is adjusted so that δ is 0.01, and the chemical formula of the obtained positive electrode active material is Li 1.01 (Ni 0.287 Co 0.0452 Li 0.122 Mn 0.531 Ti 0.007 )Al 0.010 O 2.005 F 0.010 .

[0125] Example 8

[0126] The preparation method of the positive electrode active material is the same as that in the embodiment, except that the amount of lithium carbonate is adjusted so that δ is 0.09. The chemical formula of the obtained positive electrode active material is Li 1.09 (Ni 0.287 Co 0.0452 Li 0.122 Mn 0.531 Ti 0.007 )Al 0.010 O 2.045 F 0.010 .

[0127]

[0128]

[0129] Comparative Example 1

[0130] The preparation process of the positive electrode active material is the same as that of Example 1, except that the solid-liquid ratio of the matrix material to deionized water is 0.2 g / mL.

[0131] Comparative Example 2

[0132] The preparation process of the positive electrode active material is the same as that of Example 1, except that the solid-liquid ratio of the matrix material to deionized water is 4.5 g / mL.

[0133] Comparative Example 3

[0134] The preparation process of the positive electrode active material is the same as that of Example 1, except that 2 The particle size D50 of the source is 1000 nm.

[0135] Comparative Example 4

[0136] The preparation process of the positive electrode active material is the same as that of Example 1, except that M 2 source.

[0137] Performance Testing

[0138] 1.BET specific surface area

[0139] In the present application, the testing method of BET specific surface area is: soaking the positive electrode active material in an acidic solution for 2 hours, the weight ratio of the positive electrode active material to the acidic solution is 1:10, the pH of the acidic solution is 5.5, and after soaking, vacuum drying at 120°C is performed, and the BET specific surface area is obtained by testing using Micromeritics' Tristar 3020 model specific surface area analyzer.

[0140] 2. Porosity

[0141] The pore volume was obtained by using a Micromeritics Tristar 3020 surface area analyzer, and the skeleton volume was obtained by using a Micromeritics AccuPyc 1345 density analyzer. Porosity = pore volume / (pore volume + skeleton volume) × 100%

[0142] 3. Average pore size

[0143] The surface area was measured by using the Micromeritics Tristar 3020 surface area analyzer.

[0144] 4. The proportion of pores with a diameter less than or equal to 10nm

[0145] The pore size distribution was obtained by using a Micromeritics Tristar 3020 surface area analyzer, wherein the pore size ratio was less than or equal to 10 nm.

[0146] 5. Compacted density

[0147] Obtained through testing by Japan Mitsubishi powder impedance measurement system.

[0148] 6.XRD

[0149] The results were obtained by using a Smart Lab 9KW X-ray diffractometer from Rigaku Corporation, where the FWHM of the (003) peak was calculated to have a 2θ value of 17.5°-19.5°, and the FWHM of the (104) peak was calculated to have a 2θ value of 43.5°-45.5°.

[0150] 7. First discharge specific capacity

[0151] The initial discharge specific capacity is obtained by placing the button battery for 2 hours after production. After the open circuit voltage stabilizes, the positive electrode is charged to a cut-off voltage of 4.55V at a current density of 25mA / g, and the constant voltage charging cut-off current is 0.05C. Subsequently, the battery is discharged at the same current density to a cut-off voltage of 2.5V, thus obtaining the first discharge specific capacity.

[0152] 8. Average discharge voltage

[0153] Average discharge voltage = discharge energy during discharge / discharge capacity during discharge.

[0154] 9. Volumetric energy density

[0155] Obtained through testing by Japan Mitsubishi powder impedance measurement system.

[0156] 10. Cycle capacity retention rate

[0157] After the button battery is discharged for the first time, it is charged and discharged at 0.1C twice, and the current density of the positive electrode is changed to 250mAh / g, the charging cut-off voltage is 4.55V, and the constant voltage charging cut-off current is 0.05C. Then, it is discharged at the same current density to the cut-off voltage of 2.5V, and the first cycle capacity is obtained. After 50 cycles, the 50th cycle capacity is obtained. Cycle capacity retention rate = 50th cycle capacity / first cycle capacity × 100%.

[0158] The chemical formulas of the positive electrode active materials in Examples 1 to 8 and Comparative Examples 1 to 4 are shown in Table 2, the test results of the positive electrode active materials are shown in Table 3, and the test results of the batteries are shown in Table 4.

[0159] Table 2

[0160]

[0161]

[0162] Table 4

[0163]

[0164] It can be seen from the comparison between Examples 1 to 8 and Comparative Examples 1 to 4 that in the process of preparing the positive electrode active material, the present application controls M 2 The particle size D50 of the source and the solid-liquid ratio of the matrix material to the solvent, the prepared positive electrode active material before and after immersion in the acidic solution, the average pore size less than or equal to 10nm pore size ratio increased, the average pore size of the positive electrode active material showed a decreasing trend, before and after immersion in the acidic solution, the porosity changed slightly, but the increase rate of BET specific surface area (ΔBET) was large. Using the positive electrode active material of the present application, the battery has a higher first discharge specific capacity, average discharge voltage, volume energy density and cycle capacity retention rate. This application describes that by controlling M 2 The particle size D50 of the source and the solid-liquid ratio of the matrix material to the solvent can be used to wash the soluble residual substances in the pores between the primary particles to the outside of the secondary particles during the coating process. 2 The particle size D50 of the source controls the depth and degree of flushing, so that more micropores are formed inside the secondary particles, so that after the positive electrode active material is immersed in an acidic solution, the porosity changes little, but the specific surface area increase rate (ΔBET) is large, thereby obtaining a battery with both excellent cycle performance and high volume energy density.

[0165] It can be seen from the comparison between Example 1 and Comparative Example 1 that if the solid-liquid ratio is too small, resulting in a too thin coating layer, the specific surface area of ​​the positive electrode active material after coating is larger, so the specific surface area changes little before and after immersion in the acidic solution.

[0166] It can be seen from Example 1 and Comparative Example 2 that if the solid-liquid ratio is too large, the coating layer will be too thick, the pore-forming ability inside the particles will be limited, and the specific surface area of ​​the positive electrode active material will be larger after coating. Therefore, the specific surface area changes little before and after immersion in the acidic solution.

[0167] It can be seen from Example 1 and Comparative Example 3 that if M 2 The source particle size D50 is too large, the coating agent particles are too large, and the formed coating layer is unevenly distributed on the particle surface. After coating, the specific surface area of ​​the positive electrode active material is large and the pore size is large. At the same time, the coating agent cannot enter the gap between the primary particles and cannot form an effective coating. Therefore, the increase rate of the specific surface area before and after immersion in the acidic solution is small.

[0168] It can be seen from Example 1 and Comparative Example 4 that if M is not added during the coating process 2 Source, before and after immersion in acidic solution, the increase rate of specific surface area of ​​positive electrode active material is not obvious.

[0169] It can be seen from Example 1, Example 7 and Example 8 that in the process of preparing the positive electrode active material, by adjusting the amount of lithium source added (i.e., n1 / n2), the Li content in the positive electrode active material can be regulated, and then the ratio of FWHM (104) / FWHM (003) can be controlled to obtain a positive electrode active material with better lattice integrity, thereby improving the battery's cycle capacity retention rate.

[0170] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A positive electrode active material, characterized in that: The positive electrode active material is a secondary particle formed by agglomeration of primary particles, at least part of the surface of the secondary particle has a coating layer, the secondary particle includes pores, and the positive electrode active material satisfies: ΔBET=BET2-BET1, 1m 2 / g≤ΔBET≤3.45m 2 / g, ΔP=P2-P1, 0.7%≤ΔP≤1.9%, wherein BET1 is the specific surface area of ​​the positive electrode active material before immersion in the acidic solution, BET2 is the specific surface area of ​​the positive electrode active material after immersion in the acidic solution, P1 is the porosity of the positive electrode active material before immersion in the acidic solution, P2 is the porosity of the positive electrode active material after immersion in the acidic solution, the weight ratio of the positive electrode active material to the acidic solution is 1:10, the pH of the acidic solution is 5.5, and the immersion time is 2h.

2. The positive electrode active material according to claim 1, characterized in that Satisfy at least one of the following conditions: <h2 style=";text-align:left;direction:ltr">1.75m<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> / g≤BET2≤4m<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> / g; 0.55m 2 / g≤BET1≤1.85m 2 / g。 3. The positive electrode active material according to claim 1, characterized in that Satisfy at least one of the following conditions: 1.9%≤P1≤4%; 2.6%≤P2≤6.5%。 4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The positive electrode active material satisfies: ΔDp=Dp1-Dp2, 7nm≤ΔDp≤13nm, wherein Dp1 is the average pore size of the positive electrode active material before the positive electrode active material is immersed in the acidic solution, and Dp2 is the average pore size of the positive electrode active material after the positive electrode active material is immersed in the acidic solution.

5. The positive electrode active material according to claim 4, characterized in that Satisfy at least one of the following conditions: 16nm≤Dp1≤36nm; 9nm≤Dp2≤25nm.

6. The positive electrode active material according to claim 4, characterized in that Satisfy at least one of the following conditions: Before the positive electrode active material is immersed in the acidic solution, the pore size of the positive electrode active material is less than or equal to 10 nm, accounting for 33% to 60%; After the positive electrode active material is immersed in the acidic solution, the pore size of the pores less than or equal to 10 nm accounts for 50%-80%.

7. The positive electrode active material according to claim 6, characterized in that The compaction density of the positive electrode active material is 2.7 g / cm 3 -3.2g / cm 3 .

8. The positive electrode active material according to claim 7, characterized in that The positive electrode active material satisfies: η=FWHM(104) / FWHM(003), 1.8≤η≤2.8, optionally, 1.85≤η≤2.1, wherein FWHM(104) is the half-peak width of the diffraction peak (104) of the X-ray diffraction spectrum, and the 2θ value corresponding to the diffraction peak (104) is 43.5°-45.5°, and FWHM(003) is the half-peak width of the diffraction peak (003) of the X-ray diffraction spectrum, and the 2θ value corresponding to the diffraction peak (003) is 17.5°-19.5°.

9. The positive electrode active material according to claim 1, characterized in that The positive electrode active material includes a compound shown in Formula I: Li 1+δ (Ni x(1-a) Co y(1-a) Li (1-2x-y)(1-a) / 3 Mn (2-x-y)(1-a) / 3 M 1 a M 2 b )O (2+δ / 2) N n Formula I, Among them, 0.02≤δ≤0.08, 0.25≤x≤0.45, 0≤y≤0.1, 0≤a≤0.035, 0<b≤0.04, 0≤n≤0.04, M 1 Including at least one of Al, Zr, Y, Mg, Ti, W, Si, Yb, Nb, Sc, Ca, La, Sr, Y, M 2 It includes at least one of B, Mg, Al, Ti, V, Sr, Y, Zr, Nb, Mo, Sc, Cr, La, Sr, and W, and N includes at least one of F, S, P, and O.

10. The positive electrode active material according to claim 9, characterized in that Satisfy at least one of the following conditions: 0.03≤δ≤0.06; 0.001≤a≤0.02; 0.001≤b≤0.02; 0≤n≤0.02。 11. The positive electrode active material according to claim 9, characterized in that The coating layer includes M 2 element.

12. A method for preparing a positive electrode active material, characterized in that: include: The lithium-rich manganese-based precursor, lithium source, M 1 The source mixture is mixed and sintered for the first time to obtain a matrix material; The base material, M 2 The source and solvent are mixed for coating treatment, and the M 2 The particle size D50 of the source is 20nm-700nm, the solid-liquid ratio of the matrix material to the solvent is 0.3g / mL-3.5g / mL, the solid-liquid separation is performed, and the solid phase material is dried to obtain a matrix material having a coating layer on at least a portion of the surface; The base material with the coating layer is subjected to a second sintering, wherein the temperature of the second sintering is less than or equal to the temperature of the first sintering, so as to obtain the positive electrode active material.

13. The method according to claim 12, characterized in that Satisfy at least one of the following conditions: The coating treatment temperature is 8°C-37°C; The coating treatment time is 30s-1200s, and can be optionally 60s-600s.

14. The method according to claim 12 or 13, characterized in that The molar content of lithium in the lithium source is n1, and the molar content of Ni, Co, Mn, Mn in the lithium-rich manganese-based precursor is n1. 1 The total molar content of the elements is n2, and satisfies: 1.12≤n1 / n2≤1.

49.

15. The method according to claim 12 or 13, characterized in that The M 2 Source M 2 The molar content of the element is n3, and satisfies 0≤n3 / n2≤0.05, optionally, 0.001≤n3 / n2≤0.

02.

16. The method according to claim 12 or 13, characterized in that Satisfy at least one of the following conditions: The temperature of the first sintering is 800°C-980°C; The first sintering time is 5h-15h; The heating rate of the first sintering is 1.3°C / min-10°C / min.

17. The method according to claim 12 or 13, characterized in that Satisfy at least one of the following conditions: The temperature of the second sintering is 300°C-800°C; The second sintering time is 6h-20h.

18. The method according to claim 12 or 13, characterized in that: The precursor includes a compound shown in formula II: Ni x Co y Mn z (OH)2 formula Π, Among them, 0.25≤x≤0.45, 0≤y≤0.10, z=1-xy.

19. The method according to claim 12, characterized in that Satisfy at least one of the following conditions: The M 1 Sources include M 1 Oxide, M 1 Sulfide, M 1 Fluoride, M 1 The hydroxide, M 1 at least one of the carbonates of The M 2 Sources include M 2 Oxide, M 2 Sulfide, M 2 Fluoride, M 2 The hydroxide, M 2 Carbonate, M 2 At least one of the oxyhydroxides.

20. A positive electrode plate, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 11 or the positive electrode active material prepared by the method according to any one of claims 12 to 19.

21. A battery, characterized in that: Including the positive electrode sheet as described in claim 20.

22. An electrical equipment, characterized in that: Comprising the battery of claim 21.

Citation Information

Cited By

  • Positive electrode active material and preparation method therefor, positive electrode sheet, battery, and electric device

    WO2026065637A1